2019
DOI: 10.1088/1361-648x/ab06d5
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the origin of magnetic ordering in ferroelectric BaTiO3- d thin film via electronic structure modification

Abstract: With the motive of unraveling the origin of native vacancy induced magnetization in ferroelectric perovskite oxide systems, here we explore the consequences of electronic structure modification in magnetic ordering of oxygen deficient epitaxial BaTiO 3−δ thin films. Our adapted methodology employs state-of-the-art experimental approaches viz. photoemission, photo-absorption spectroscopies, magnetometric measurements duly combined with first principles based theoretical methods within the frame work of density … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…On the other hand, the possible presence O vacancy in lattice structure will modify the ligand field symmetry and electron hole ratio in transition metal d band. Consequently, the spectral shape and intensity of feature λ is a sensitive probe for the lattice oxygen content of the system [54,55]. We have observed that for different SNMO films with varying growth conditions, feature λ in O K XANES show similar spectral shape and weight (Inset of Fig.…”
Section: Resultsmentioning
confidence: 81%
“…On the other hand, the possible presence O vacancy in lattice structure will modify the ligand field symmetry and electron hole ratio in transition metal d band. Consequently, the spectral shape and intensity of feature λ is a sensitive probe for the lattice oxygen content of the system [54,55]. We have observed that for different SNMO films with varying growth conditions, feature λ in O K XANES show similar spectral shape and weight (Inset of Fig.…”
Section: Resultsmentioning
confidence: 81%
“…NPD refinement of Ni and Mn occupancies at 2c and 2d sites, reveals presence of ∼3.8(6)% and 11.8(8)% ASD in S O and S D samples, respectively. As the vacancy defects may influence the electronic and magnetic properties [36], it is also important to check the possible presence of cation or anion vacancy defects in SNMO system. The scattered X-ray intensity in PXRD measurements depend on electron density of the scattering atom, hence the contributions from heavy Z elements dominate over low Z elements and any attempt to determine atomic concentration of low Z element such as oxygen could be erroneous.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we plan to investigate the EB effect in Sm 2 NiMnO 6 /BaTiO 3 /Sm 2 NiMnO 6 (SBS) heterostructure. Assuming the ideal scenario (defect free crystal structure) Sm 2 NiMnO 6 (SNMO) and BaTiO 3 (BTO) can be categorized as FM and diamagnetic systems due to Ni 2+/3+ -O-Mn 4+/3+ near linear super exchange interaction and Ti 4+ 3d 0 configuration, respectively [16,17]. However, in our previous studies we have observed that presence of defects in SNMO and BTO host matrix has huge bearings on their corresponding magnetic behaviors [17,18].…”
mentioning
confidence: 99%
“…Assuming the ideal scenario (defect free crystal structure) Sm 2 NiMnO 6 (SNMO) and BaTiO 3 (BTO) can be categorized as FM and diamagnetic systems due to Ni 2+/3+ -O-Mn 4+/3+ near linear super exchange interaction and Ti 4+ 3d 0 configuration, respectively [16,17]. However, in our previous studies we have observed that presence of defects in SNMO and BTO host matrix has huge bearings on their corresponding magnetic behaviors [17,18]. Here, we have demonstrated how defect induced alteration in electronic structure can drive unusual magnetic behavior like EB phenomenon in SBS heterostructure system.…”
mentioning
confidence: 99%
See 1 more Smart Citation